The Effect Catheter Care on Length of Catheter Installation - Wardah Fauziah; Aat Agustini; Novian Mahayu Adiutama (Universitas STRADA Indonesia, 2022)
Background: Urinary tract infections may increase the prevalence of healthcare-associated infections, which reaches 40%. Catheter Associated Urinary Tract Infections (CAUTI) can cause unnecessary postoperative morbidity, and increase the length of stay and mortality, which can lead to complications of urosepsis and even death. Many interventions of evidence-based nursing are practiced by nurses to prevent CAUTI. One of them is catheter care based on evidence-based nursing. Purpose: The study aimed to determine the effects of catheter care on the duration of catheter installment. Methods: The research described a quantitative study with a quasi-experimental approach with post-test only design with control group. The samples were 66 patients, consisting of 33 patients in the intervention group and 33 patients in the control group. Results: Data were collected using observation sheets and analyzed using Fisher E and Mann Whitney tests. Conclusion: The duration of catheter installment in the control group and the intervention group was 5-11 days and 4-8 days, respectively. Catheter of care could reduce the duration of catheter installment.